PI3 kinase signaling pathway in hematopoietic cancers: A glance in miRNA's role. Issue 4 (5th March 2021) - Roshandel, Elham; Noorazar, Leila; Farhadihosseinabadi, Behrouz; Mehdizadeh, Mahshid; Kazemi, Mohammad Hossein; Parkhideh, Sayeh
Abstract: Hematopoietic cancers are among the most common malignancies worldwide, which are divided into different types depending on the origin of tumor cells. In recent years, the pivotal role of different signaling pathways in the onset and progression of these cancer types has been well established. One of these pathways, whose role in blood malignancies has been well‐defined, is PI3K/mTOR/AKT axis. The signaling pathway involves in a wide variety of important biological events in cells. It is clear that dysregulation of mediators involved in PI3 kinase signaling takes a pivotal role in cancer development. Considering the undeniable role of miRNAs, as one of the well‐known families of non‐coding RNAs, in gene regulation, we aimed to review the role of miRNAs in regulation of PI3 kinase signaling effectors in hematopoietic cancers. Abstract : PI3K pathway involves in a wide verity of important biological events in cells such as proliferation, differentiation, apoptosis, and even drug resistance. It is confirmed that there is a relationship between dysregulation of mediators involved in this signaling pathway and different cancer types such as hematopoietic malignancies. Considering the pivotal role of miRNAs as the key regulators in gene regulation, overexpression and downregulation of various miRNAs have been reported to take a role in development of different hematopoietic cancers through targeting mediators of PI3K signaling pathway.